INTEGRATING INTERCULTURAL COMMUNICATION IN ENGLISH LANGUAGE CURRICULUM - Dias, Naveen A. H (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The book discusses how one’s culture produces unconscious behaviours that allow others to read messages that are being sent unknowingly: the "Silent Language." It was written in 1959 book and was meant for lay readers and for professionals in the fields of anthropology and linguistics, and is relevant now in this modern age also. In many cases, Hall offers examples of real-world situations that clarify difficult passages in the text. The Silent Language is a work of interest to both the intelligent general reader and the sophisticated social scientist. The author, a leading anthropologist, analyses the many aspects of non-verbal communication and considers the concepts of space and time as tools for transmission of messages in this fascinating study.